IMPLEMENTATION OF C4.5 ALGORITHM FOR ASSESMENT OF COMMUNITY SATISFACTION - Sulaiman, Rahmat; Raya, Agustina Mardeka; Laurentinus; Setiawan, Aria (Pusat Riset dan Inovasi Nasional, 2023)
This Research applies the C4.5 Algorithm in deciding community satisfaction of sommunity services. Algorithm C4.5 is a classification algorithm with a decision tree technique that is well known and preferred because it has many advantages. These advantages, for example, can process numeric and discrete data, can handle missing attribute values, produce rules that are easy to interpret and the fastest. This research is a classification with the concept of data mining involving 20 community questionnaire data which are categorized as: cheap, expensive, appropriate, inappropriate, fast, long, comfortable, uncomfortable. There are four attributes that affect community satisfaction including: handling costs, service procedures, handling time and convenience. From the results of this research that has been conducted by researchers, it can be concluded. The customer satisfaction of the community services can be predicted and evaluated by utilizing data mining techniques using the C4.5 Algorithm to predict community satisfaction. This research also provided that C4.5 Algorihtm can be used to get high result of accuracy